A place of healing : wrestling with the mysteries of suffering, pain, and God's sovereignty - Tada, Joni Eareckson (Colorado Springs, CO : David C. Cook, 2010)
Over four decades ago, a diving accident left Joni Eareckson Tada a quadriplegic. Since that time, she has become a beloved writer and speaker to millions. But today, Joni faces a new battle: chronic, unrelenting pain. As she writes, "Just as I said to God years ago when I was first injured, I find myself praying, Lord, I can't live like this for the rest of my life! This ongoing urgency has forced me to look back on familiar scriptures and examine them from new angles. Does God miraculously intervene in the lives of all who pray for release from migraine headaches, multiple sclerosis, cancer or, in my case, chronic pain? And if not, why not?" Here Joni invites you to walk with her through an intense and baffling season of her life. Her words offer not a bundle of ivory-tower theological conclusions but intimate insight from a woman on a journey a woman who believes in healing from a God who chooses when that healing will come -- Publisher description.
Report from the front lines -- God and healing : what's the real question? -- Healer-and Lord -- What benefit is there to my pain? -- How can I go on like this? -- How can I bring him glory? -- How do I regain my perspective? -- Ultimate healing -- Suffering--and the harvest -- Thank you, God, for this wheelchair
Includes bibliographical references (p.211-216).
Keywords: Suffering -- Religious aspects -- Christianity; Christian life; Theodicy; Spiritual healing